The building types and building culture in accordance to the relationship between human, environment and culture - Çopuro?lu, Y. Cemalettin (My University, 2003)
Sheltering is one of the basic human needs and the most basic socio-cultural element as it contains home culture and family life. From this point it is the fact that occurs by the most concrete and complex living of the human, environment and culture interaction. So, the cultural elements had been tried to determine what they mean in the society of Euphrates Basin.
İnsan, çevre, kültür etki?leşi?mi? çerçevesi?nde barinma kültürü
Keywords: Culture; Euphrates Basin; Home; Sheltering